Divergent Landlord-Tenant Regimes: A Comparative Analysis of Legal Frameworks and Eviction Practices in Nigeria's Urban Centres (Edo and Lagos States) - Omoigberale, Omonye (ABUAD Law Journal, 2025)
This study examined the contrasting legal frameworks governing landlord-tenant relationships in two key Nigerian urban centers: Edo and Lagos States. It critically examined the Rent Control and Recovery of Residential Premises Law of Edo State, Cap R1 1977 (RCRPL), the Lagos State Tenancy Law 2011 (TL), relevant case law, and secondary sources to uncover significant disparities in eviction protocols, rent regulation, and dispute resolution mechanisms. The analysis reveals the TL’s comparatively robust framework, which incorporates more extensive Alternative Dispute Resolution (ADR) options, in contrast to the outdated provisions of the RCRPL. Furthermore, the findings underscore the widespread underutilization of formal legal mechanisms and the persistence of informal eviction practices in both states, which erode tenant protections and perpetuate housing insecurity. Anchored in the theoretical perspectives of legal pluralism and socio-legal studies, the research situates these findings within Nigeria's complex legal, social, and economic milieu. The study advocates for harmonized legislative reforms, including a comprehensive revision of the RCRPL to align with contemporary realities, enhanced public awareness of legal rights, and strengthened enforcement frameworks. These interventions are imperative for fostering equitable landlord-tenant relations, advancing housing security, and contributing to sustainable urban development and social justice in Nigeria.